(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
It is intended by the command, governing bodies, commander and their deputies (service chiefs) to know deeply the spirituality, level of knowledge, family situation and behavior, characteristics, actions and discipline in the community, and their specifics. The article discusses the organization of individual educational work with personal content.